Analisis Konten: Lagu "Ajaib" (Gempita Nora Marten) terhadap Pendidikan Karakter Anak di Sekolah Dasar - Rosie Amelia; Alya Awwaliyatin Kuswandi; Najwa Pitriani; Mochamad Ilham Abdillah; Salvia Nasywa Prabawa; Teten Ginanjar Rahayu (Tambuleng, 2026)
This study was motivated by the urgent need to strengthen character education for elementary school students amid increasing exposure to digital content that is not entirely educational. Children’s music has pedagogical potential, yet research on contemporary songs remains limited. This study aims to analyze the character education values in the song “Ajaib” by Gempita Nora Marten and its relevance as a medium for contextual learning. The method used is qualitative, involving content analysis of the lyrics and music video, through the stages of unitizing, sampling, coding, and inferring based on categories of national character values. The results reveal six main values: cooperation, independence, integrity, religiosity (implicit), empathy, and a positive attitude. The value of mutual cooperation is dominant, while other values appear implicitly yet consistently. Pedagogically, the simple and repetitive structure of the lyrics supports the internalization of values through students’ affective and cognitive engagement. This study affirms that popular children’s songs can serve as an effective, contextual educational medium aligned with the, and has the potential to enhance character education holistically.